2019
DOI: 10.1073/pnas.1817322116
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic organs shaped by distinct modes of genome evolution in cephalopods

Abstract: Microbes have been critical drivers of evolutionary innovation in animals. To understand the processes that influence the origin of specialized symbiotic organs, we report the sequencing and analysis of the genome of Euprymna scolopes, a model cephalopod with richly characterized host–microbe interactions. We identified large-scale genomic reorganization shared between E. scolopes and Octopus bimaculoides and posit that this reorganization has contributed to the evolution of cephalopod complexity. To reveal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
194
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(207 citation statements)
references
References 35 publications
13
194
0
Order By: Relevance
“…The large number of assembled transcripts is a common trait found in other de novo assembled transcriptomes of E. scolopes (43,44). Cephalopods are known to expand certain gene families (45,46). This feature, together with the high levels of heterozygosity and transcript editing (47) that are known to challenge assembly software (48), contributed to the high number of observed expressed transcripts.…”
Section: Resources For Analyses Of Symbiosis Effects On Host Gene Expmentioning
confidence: 99%
“…The large number of assembled transcripts is a common trait found in other de novo assembled transcriptomes of E. scolopes (43,44). Cephalopods are known to expand certain gene families (45,46). This feature, together with the high levels of heterozygosity and transcript editing (47) that are known to challenge assembly software (48), contributed to the high number of observed expressed transcripts.…”
Section: Resources For Analyses Of Symbiosis Effects On Host Gene Expmentioning
confidence: 99%
“…A recent study of the Hawaiian bobtail squid ( Euprymna scolopes ), has shown that its light organ (LO), a specialized symbiotic structure that houses luminescent bacteria, expresses tandemly duplicated genes (i.e., reflectins) . Another symbiotic organ present in many squid species, the accessory nidamental gland (ANG), was found to be enriched in novel genes . Same scenario was found for other tissues, such as suckers of Octopus bimaculoides .…”
Section: Cephalopods: Model Systems For the Study Of Genome Evolutionmentioning
confidence: 94%
“…Only recently could genomic studies of cephalopods be accomplished . Large and repetitive genomes were hindering sequencing and assembly .…”
Section: Cephalopods: Model Systems For the Study Of Genome Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27,46,92,104,105,107,108]), nemerteans [89], molluscs (e.g. [30,36,41,92,107,[109][110][111][112]) and possibly kamptozoans [113] (however, in the latter the lox2-like sequence lacks most of the residues considered as lox2 signature; Additional file 1: Fig. S1).…”
Section: Hox Gene Complement In Phoronidamentioning
confidence: 99%